Prophetic Character Education Through Audiovisuals for Elementary School Students - Galuh Nashrulloh Karika MR; Barsihanor Barsihanor; Siti Nurul Ain Binti Mohd Yusoff; Norhayati binti Haji Abdul Karim; Raihatul Jannah (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study aims to describe prophetic character education in the animated film Riko The Series episode 08 and its relevance for character education for elementary school children. This qualitative study uses content analysis to analyze the message's meaning and how to reveal the message. Technically, this research method is carried out by processing information documented in recordings, either images, sounds, writing, or other forms of recordings from the animated film Riko The Series episode 08, then analyzed based on the theory of prophetic character education and the theory of tadabbur Al-Qur'an, namely interpreting the explicit meaning with implicit understanding. The results of this study state, 1) there are two implicit meanings of the message of the Al-Qur'an surah an-Nur verse 22 that are relevant to prophetic character education for elementary school children in the animated film Riko The Series episode 08, namely the phrase falya'fu which is relevant to the forgiving character and the phrase falyashfahu which is relevant to the broad-minded character. The forgiving and broad-minded characters are in accordance with Alexistoto the prophetic character education theory proposed by Moh. Roqib, a humanist prophetic character, eliminates various forms of violence and hatred towards others because both of these things will damage human values. 2) there is a strong relevance between the animated film Riko The Series episode 08 and prophetic character education for elementary school children in Indonesia, as evidenced by the existence of Presidential Regulation No. 87 of 2017 concerning Strengthening Character Education implemented in Elementary Schools.